CT reconstruction from simultaneous projections: a step towards capturing CT in One Go. Issue 2 (4th March 2017) - Saha, Sajib Kumar; Tahtali, Murat; Lambert, Andrew; Pickering, Mark
Abstract : This paper focuses on minimising the time requirement for CT capture through an innovative simultaneous X-ray capture method. The state-of-the-art CT-imaging methodology captures a sequence of projections during which the internal organ movements may lead to poor reconstruction due to motion artefacts. Traditional CT scanners minimise such effects by taking extra projections. In this work, we focus on an innovative CT capture method that captures projections simultaneously, thus significantly minimises the scan time. Through ensuring rapid scan, the proposed method eliminates the extra projections that are needed to compensate for motion artefacts. By requiring a less number of projections, the simultaneous CT capture model ultimately minimises the radiation dose requirement. While the simultaneous CT capture model has already been proposed in our earlier works [Saha S, Tahtali M, Lambert A, Pickering M. 2012. Multi-axial CT reconstruction from few view projections. In: SPIE optical engineering+applications. USA: International Society for Optics and Photonics; p. 85000A–85000A and Tahtali M, Saha SK, Lambert AJ, Pickering MR. 2013. A new imaging method for real-time 3D X-ray reconstruction. In: SPIE medical imaging. International Society for Optics and Photonics; p. 86685G–86685G], in this work, we enhance the model through better initialisation along with prior smoothing before successive iterations of the iterative algorithms. We also elaborate the model considering two different X-ray source/detector configurations. For the same number of X-ray sources in total, set-up II (which considers eight angular projections) ensures better cross-section reconstruction compared to set-up I (which considers only four angular projections). In addition to simulation experiments, we present results from real experimental data from a physical 3D object, and critical analysis of the experimental findings